Is the true clinical value of high-sensitivity troponins as a biomarker of risk? The concept that detection of high-sensitivity troponin 'never means nothing'. (1st December 2020) - Hinton, Jonathan; Gabara, Lavinia; Curzen, Nick
ABSTRACT: Introduction: High-sensitivity troponin (hs-cTn) assays are central to the diagnosis of myocardial infarction (MI). Their increased sensitivity has facilitated rapid pathways for the exclusion of MI. However, hs-cTn is now more readily detectable in patients without symptoms typical of MI, in whom a degree of myocardial injury is assumed. Recently, the practice of using the 99 th centile of hs-cTn as a working 'upper reference limit' has been challenged. There is increasing evidence that hs-cTn may provide useful prognostic information, regardless of any suspicion of MI, and as such these assays may have potential as a general biomarker for mortality. This raises the concept that detection of hs-cTn 'never means nothing.' Areas covered: In this review, we will evaluate the evidence for the use of hs-cTn assays outside their common clinical indication to rule out or diagnose acute MI. Expert opinion: The data presented suggest that hs-cTn testing may in the future have a generalized role as a biomarker of mortality risk and may be used less as a test for ruling in acute MI, but will remain a frontline test to exclude that diagnosis in ED. Further, the data suggest that the detection of hs-cTn 'never means nothing.'